Photonics and optoelectronics of two-dimensional materials beyond graphene. (24th October 2016) - Ponraj, Joice Sophia; Xu, Zai-Quan; Dhanabalan, Sathish Chander; Mu, Haoran; Wang, Yusheng; Yuan, Jian; Li, Pengfei; Thakur, Siddharatha; Ashrafi, Mursal; Mccoubrey, Kenneth; Zhang, Yupeng; Li, Shaojuan; et al.
Abstract: Apart from conventional materials, the study of two-dimensional (2D) materials has emerged as a significant field of study for a variety of applications. Graphene-like 2D materials are important elements of potential optoelectronics applications due to their exceptional electronic and optical properties. The processing of these materials towards the realization of devices has been one of the main motivations for the recent development of photonics and optoelectronics. The recent progress in photonic devices based on graphene-like 2D materials, especially topological insulators (TIs) and transition metal dichalcogenides (TMDs) with the methodology level discussions from the viewpoint of state-of-the-art designs in device geometry and materials are detailed in this review. We have started the article with an overview of the electronic properties and continued by highlighting their linear and nonlinear optical properties. The production of TIs and TMDs by different methods is detailed. The following main applications focused towards device fabrication are elaborated: (1) photodetectors, (2) photovoltaic devices, (3) light-emitting devices, (4) flexible devices and (5) laser applications. The possibility of employing these 2D materials in different fields is also suggested based on their properties in the prospective part. This review will not only greatly complement the detailed knowledge of the device physics of these materials, but also provide contemporary perception for the researchers who wish to consider these materials for various applications by following the path of graphene.